Near‐Infrared II Dye‐Protein Complex for Biomedical Imaging and Imaging‐Guided Photothermal Therapy. Issue 18 (26th July 2018) - Zeng, Xiaodong; Xiao, Yuling; Lin, Jiacheng; Li, Shanshan; Zhou, Hui; Nong, Jinxia; Xu, Guozhen; Wang, Hongbo; Xu, Fuchun; Wu, Junzhu; Deng, Zixin; Hong, Xuechuan
Abstract: The development of novel biodegradable and nontoxic fluorophores that integrate diagnosis and therapy for effective cancer treatment has obtained tremendous attention in the past decades. In this report, water‐soluble and biocompatible small‐molecule near‐infrared II (NIR‐II) fluorescent dye H2a‐4T complexed with fetal bovine serum (FBS) and Cetuximab proteins with excellent optical properties and targeting ability is prepared. High spatial and temporal resolution imaging of hind limb vasculature and the lymphatic system of living mice using H2a‐4T@FBS complex is demonstrated in precise NIR‐II imaging‐guided sentinel lymph node surgery. More importantly, H2a‐4T@Cetuximab complex not only exhibits a remarkable cell‐killing ability but also achieves highly active tumor targeting efficiency for epidermal growth factor receptor, overexpressing colorectal cancer which is beneficial to in vivo NIR‐II fluorescent imaging‐guided photothermal therapy of colon tumors. To the best of our knowledge, it is the first time that the concept of light‐harvesting complex is exploited for enhancing the NIR‐II signals and photothermal energy conversion in molecule‐protein complex theranostic agent, making them a promising candidate for future clinical applications in cancer theranostics. Abstract : The first light‐harvesting complex produced by noncovalent interaction between a small‐molecule organic NIR‐II fluorophore and proteins is facilely assembled and used for not only NIR‐II fluorescent imaging of hind limb vasculature and lymphatic system, but also NIR‐II imaging‐guided lymph node surgery and photothermal therapy.